Silanization of nanographene platelets improves interaction with the dentin bonding resin matrix and enhances interfacial bond integrity to dentin. (16th November 2021) - Akram, Zohaib; Aati, Sultan; Shrestha, Barsha; Clode, Peta; Saunders, Martin; Ngo, Hien; Fawzy, Amr
Abstract : Synthesis and characterization of GNP and MPS-GNP to study their interaction within the resin matrix of dentin bonding agent, biological, and mechanical properties of the bonded specimens. Abstract : This study synthesized and characterized graphene nanoplatelets silanized with 3-(trimethoxysilyl)propyl methacrylate (MPS-GNP) for morphological and chemical characteristics. In addition, we modified a dentin bonding agent using different concentrations of MPS-GNP to study its interaction within the resin matrix of the adhesive, degree of conversion (DC), biological, and mechanical properties after bonding to tooth. Both 0.25% and 0.5% MPS-GNP-modified bonding agents showed comparable DC values to the unmodified control adhesive (range: 41%–43%). However, a statistically significant reduction in the DC was found when 0.25% and 0.5% non-silanized GNP was doped with the adhesive (<38%) ( p < 0.05). On day 30, the bacterial viability of 0.5% GNP and MPS-GNP groups remained very low under 22% with the highest dead cell count ( p < 0.05). GNP incorporated within the resin matrix of the dentin bonding agent showed clear evidence of several interfacial gap formations and non-union between the GNP surface and resin matrix, while the MPS-GNP modified dentin bonding agent showed MPS-GNP with no gap formation with complete union between the graphene surface and resin matrix. The decrease in the μTBS was least pronounced for 0.25% and 0.5% MPS-GNP groups. After 12 months of ageing, the groups 0.25% and 0.5% MPS-GNP also showed the highest BS as compared to the rest of the groups. Statistically significant reduction was seen in nanohardness at the hybrid layer and adhesive layer for GNP groups after 4 months of storage. The addition of up to 0.5% MPS-GNP showed optimized DC, antibiofilm activity, and micro-tensile bond strength without affecting the standard adhesion characteristics as compared to GNP alone.